APPROPRIATE APPLICATION OF EQUIVALENT UNITS IN THE TRANSLATION OF HISTORICAL WORKS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article compares the Turkmen translation of the novel “Yulduzli tunlar”, which belongs to the pen of Pirimkul Kadyrov, and gives a comparative analysis about the problem of choosing an alternative word in sister languages.